Long-term safety and efficacy of tezepelumab in people with severe, uncontrolled asthma (DESTINATION): a randomised, placebo-controlled extension study - Menzies-Gow, Andrew; Wechsler, Michael E; Brightling, Christopher E; Korn, Stephanie; Corren, Jonathan; Israel, Elliot; Chupp, Geoffrey; Bednarczyk, Artur; Ponnarambil, Sandhia; Caveney, Scott; Almqvist, Gun; Gołąbek, Monika; et al. (The lancet. Respiratory medicine, 2023)
Background - Tezepelumab is a human monoclonal antibody that blocks thymic stromal lymphopoietin. The drug has been tested previously in the phase 3 NAVIGATOR (NCT03347279) and SOURCE (NCT03406078) studies, and was subsequently approved as a treatment for severe asthma. This extension study recruited from NAVIGATOR and SOURCE and aimed to evaluate the long-term safety and efficacy of tezepelumab in individuals with severe, uncontrolled asthma. - Methods - DESTINATION was a phase 3, multicentre, randomised, double-blind, placebo-controlled, long-term extension study. The study was done across 182 sites (including hospitals, clinics, medical centres, clinical trial centres, and private practices) in 18 countries. Participants (aged 12-80 years) were required to have good treatment compliance in the parent study. Randomisation was stratified by the parent study and all participants were re-randomised. Those who were previously randomised to receive tezepelumab in either parent study continued treatment of subcutaneous tezepelumab (210 mg every 4 weeks); those who were previously randomised to receive placebo in either parent study were re-randomised 1:1 to receive either subcutaneous tezepelumab (210 mg every 4 weeks) or placebo (every 4 weeks) using a randomisation list prepared by a computerised system. Total treatment duration (including the parent studies) was 104 weeks for all groups. Participants, investigators, and site staff were masked to treatment assignment. The primary endpoints were exposure-adjusted incidence of adverse events and serious adverse events and the secondary endpoint was the annualised asthma exacerbation rate; these were assessed from week 0 of the parent studies to week 104 of DESTINATION in all participants who were randomised and who received at least one dose of tezepelumab or placebo in either of the parent studies. The trial is registered with ClinicalTrials.gov, NCT03706079, and is closed to new participants. - Findings - Participants were recruited between Jan 7, 2019, and Oct 15, 2020. For individuals who initially received tezepelumab (n=528) in NAVIGATOR, incidence of adverse events over 104 weeks was 49·62 (95% CI 45·16 to 54·39) per 100 patient-years, compared with 62·66 (56·93 to 68·81) for those receiving placebo (n=531; difference −13·04, 95% CI −17·83 to −8·18). For serious adverse events, incidence was 7·85 (6·14 to 9·89) per 100 patient-years for individuals who initially received tezepelumab and 12·45 (9·97 to 15·35) for those who received placebo (difference −4·59, −7·69 to −1·65). In SOURCE, incidence of adverse events was 47·15 (36·06 to 60·56) per 100 patient-years for those who initially received tezepelumab (n=74) and 69·97 (54·54 to 88·40) for those who received placebo (n=76; difference −22·82, −34·77 to −10·01). For serious adverse events, incidence was 13·14 (7·65 to 21·04) per 100 patient-years for those who initially received tezepelumab and 17·99 (10·66 to 28·44) for those who received placebo (difference −4·85, −14·88 to 4·53). Tezepelumab reduced the annualised asthma exacerbation rate over 104 weeks compared with placebo. In participants initially from NAVIGATOR, the annualised asthma exacerbation rate ratio over 104 weeks was 0·42 (95% CI 0·35 to 0·51); in those initially from SOURCE, the ratio over 104 weeks was 0·61 (0·38 to 0·96). - Interpretation - Tezepelumab treatment was well tolerated for up to 2 years and resulted in sustained, clinically meaningful reductions in asthma exacerbations in individuals with severe, uncontrolled asthma. These findings are consistent with previous randomised, placebo-controlled studies and show the long-term safety and sustained efficacy of tezepelumab in individuals with severe, uncontrolled asthma. - Funding - AstraZeneca and Amgen.